Penggunaan Aplikasi Mobile Eating Learning “M-EL” bagi Ibu sebagai Pola Asuh Autoritatif Upaya Kemandirian saat Anak Makan - Kirana, Desi Nindya; Safitri, Yunni (Journal of Telenursing (JOTING), 2024)
This study aims to determine the use of M-El Mobile Eating Learning applications for mothers as parenting authorities of independence when children eat. This research method uses a combination of methods, namely the System Development Life Cycle (SLDC) Waterfall to design software in M-El mobile applications. The results showed that the use of M-El applications was effective in parenting (p-value 0.001) independence (p-value 0.031) and the BMW method (p-value 0.001), where the value of p-value <0.05. Before the mother is given the mobile eating learning application, the mother does not know the importance of applying authoritative parenting, the mother does not apply authoritative parenting, the child is not independent when eating because of bad habits when eating children are always fed and the mother never uses the BLW method when the child eats so Children are not independent eating. In conclusion, the use of M-El applications is effective in improving parenting, independence, and BLW method for independence efforts when children eat, so this application can be applied more broadly for children's independence efforts when eating. Keywords: Mobile Applications, Eating Learning, Children's Independence, Parenting